2014
DOI: 10.1016/j.febslet.2014.10.040
|View full text |Cite
|
Sign up to set email alerts
|

MiR‐20a regulates the PRKG1 gene by targeting its coding region in pulmonary arterial smooth muscle cells

Abstract: a b s t r a c tChronic hypoxia triggers pulmonary vascular remodeling, which is associated with de-differentiation of pulmonary artery smooth muscle cells (PASMC). Here, we show that miR-20a expression is up-regulated in response to hypoxia in both mouse and human PASMC. We also observed that miR-20a represses the protein kinase, cGMP-dependent, type I (PRKG1) gene and we identified two crucial miR-20a binding sites within the coding region of PRKG1. Functional studies showed that miR-20a promotes the prolifer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 45 publications
0
12
0
Order By: Relevance
“…RT-qPCR (Bio-Rad iQ SYBR Green) was performed to analyze relative gene expression of PKG. According to the standard protocol for SYBR Green, the following primers were utilized: PKG: 5-CCG AAT TCT GTA TTT CTC TTA CCT GCT TC-3 (forward), CAC ACT AGT GGA CTC AGT TTA ATT TGT GG (reverse) [28]. Primers utilized for SYBR Green, were synthetized by Integrated DNA Technologies.…”
Section: Methodsmentioning
confidence: 99%
“…RT-qPCR (Bio-Rad iQ SYBR Green) was performed to analyze relative gene expression of PKG. According to the standard protocol for SYBR Green, the following primers were utilized: PKG: 5-CCG AAT TCT GTA TTT CTC TTA CCT GCT TC-3 (forward), CAC ACT AGT GGA CTC AGT TTA ATT TGT GG (reverse) [28]. Primers utilized for SYBR Green, were synthetized by Integrated DNA Technologies.…”
Section: Methodsmentioning
confidence: 99%
“…[15]. PASMCs at passage 3 or 4 were used for experiments, and the contractile phenotype was confirmed by the determination of contractile marker genes expression, such as a-SMA and SM22 [16]. Growth factors including PDGFBB, AngII, TGF-b, IGF, VEGF, ET-1, PDGFAA and FGF were obtained from R&D Systems.…”
Section: Methodsmentioning
confidence: 99%
“…There is now accumulating evidence suggesting that microRNAs (miRNAs), a class of small endogenous non-coding RNA, can be essential in regulating PASMCs function [1016]. MiRNAs are known to negatively regulate gene expression by mainly interacting with the 3′-untranslated region (UTR) of their target mRNAs [1012].…”
Section: Introductionmentioning
confidence: 99%
“…Freedman suggested that GUCY1A3 mutations were related to thrombosis (53). Zeng et al indicated that miR-20a regulates the PRKG1 gene, thereby promoting the proliferation, and contributes to thrombosis (54). TNF receptor superfamily members 10B, 10C, 10D and TNFSF10 linked to inflammation and coagulation and contribute to VTE (55).…”
Section: Discussionmentioning
confidence: 99%